Regimes of legality : ethnography of criminal cases in South Asia. - Berti, Daniela; Bordia, Devika (New Delhi : Oxford University Press, 2015)
An anthropological study on judicial practices in South Asia, this volume takes criminal cases as frameworks to examine power dynamics within a legal setting. Case studies in this book analyse a set of state and non-state institutions and the practices of people associated with them. The essays delve into the underlying tension in institutional contexts between legal practitioners such as police officers, lawyers, and judges who orient their claims towards neutralism, objectivity, and equality and a set of everyday interactions and decisions where cultural, social, and political factors play a major role.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on July 21, 2015).
Keywords: Criminal justice, Administration of -- Social aspects -- South Asia